Assessing fidelity of design and training of Making Every Contact Count (MECC) in a mental health inpatient setting - Emma Kemp; Maria Raisa Jessica Aquino; Rob Wilson; Milica Vasiljevic; Kate McBride; Craig Robson; Sally Faulkner; Mish Loraine; Jill Harland; Catherine Haighton; Angela Rodrigues (BMC, 2024)
Abstract Background Making Every Contact Count (MECC) is a public health strategy which strives to enable brief interventions to be implemented through opportunistic healthy lifestyle conversations. In a mental health inpatient setting a bespoke MECC training package has been developed to encourage cascade training through a train the trainer model and to incorporate an additional regional health strategy A Weight Off Your Mind into Core MECC training to provide a focus on healthy weight management. This study evaluated the fidelity of design of MECC in the mental health inpatient setting and fidelity of the training package currently being cascaded across the region. Methods Initially a documentary analysis of six documents shared through the mental health inpatient setting including MECC implementation guide, logic model, checklist and evaluation framework. Documents were analysed using the Template for Intervention Description and Replication (TIDieR) checklist and coded using the Behaviour Change Technique (BCT) Taxonomy version one (BCTTv1) and the Expert Recommendations for Implementing Change (ERIC) Taxonomy. Coding was compared against MECC guidance documents to complete the fidelity assessment. A training delivery guide, training slides and two recordings of both train the trainer and Core MECC + A Weight Off Your Mind training were analysed for behaviour change techniques (BCTs) and compared to conduct a fidelity training assessment. Results Overall the implementation of MECC in the mental health inpatient setting had moderate fidelity to the MECC guidance, with a total of 31 BCTs identified across guidance and provider documents and a 77% adherence of provider documents to guidance. The highest level of fidelity applied to the MECC implementation guide where 86% of identified BCTs were also present. The training package showed high fidelity that both training programmes were being delivered as intended with 100% of BCT matched from training materials to training transcripts. Potential loss of fidelity through additional BCTs was present across provider documents and training transcripts. Conclusion The implementation of MECC across the mental health inpatient setting and the training package appear to be delivered as intended therefore demonstrating good fidelity and potential benefits to public health. Future research would benefit from assessing cascade training sessions from those who have completed train the trainer to evaluate ongoing fidelity of training across the trust.